2003
DOI: 10.1046/j.1365-2141.2003.04362.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognosis of c‐KIT and FLT3 mutations in core binding factor (CBF) acute myeloid leukaemias

Abstract: Summary. DNA from 110 adult de novo acute myeloid leukaemia (AML) patients exhibiting either inv(16) (n ¼ 63) or t(8;21) (n ¼ 47) was screened for mutations in the c-KIT (exon 8 and Asp816) and FLT3 (ITD and Asp835) genes. c-KIT exon 8 mutations were found in 15/63 (23AE8%) inv(16) patients and 1/47 (2AE1%) t(8;21) patients. c-KIT Asp816 mutations were present in 5/63 (7AE9%) inv(16) AML and 5/47 (10AE6%) t(8;21) AML. FLT3 mutations were identified in five patients (7AE9%) with inv(16) and three patients (5AE6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
220
5
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(232 citation statements)
references
References 13 publications
(15 reference statements)
5
220
5
2
Order By: Relevance
“…Similarly, regarding the impact on outcome, this research article study showed that KIT mutations did not reach a significative value as independent prognostic factor for relapse and survival neither in the multivariate nor in the Kaplan-Meier analysis, in contrast to those reported in adult patients with t(8;21) (Figs. 1B-2B; Tables III and IV) [24,[26][27][28][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, regarding the impact on outcome, this research article study showed that KIT mutations did not reach a significative value as independent prognostic factor for relapse and survival neither in the multivariate nor in the Kaplan-Meier analysis, in contrast to those reported in adult patients with t(8;21) (Figs. 1B-2B; Tables III and IV) [24,[26][27][28][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have demonstrated that the presence of KIT mutations in exon 17 have been associated with a poor outcome in CBF-AML and, for that reason, KIT mutation testing has been recently incorporated into National Cancer Guidelines to better stratify such patients in different prognostic subgroups [25]. However, while several studies showed that activating KIT mutations confer a significantly lower survival in AML with t(8;21)(q22;q22), the negative prognostic impact of KIT mutations in CBFb-AML remains controversial [24,[26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…50 Gain-of-function mutations may affect either the extracellular portion of c-KIT receptor, believed to play a role in the dimerization (in-frame insertion/deletions of exon 8 that all result in loss of the acid aspartic residue at amino acid 419), or the JMD (ITD of exon 11), or the structure of the AL in the TKD, such as the substitution of a single amino acid in exon 17 (mostly mutation D816V, and less commonly other mutations affecting codon 816 (D816Y/H/F/I), 821, 822 or 823). [51][52][53][54] Codon 816 c-KIT mutations were shown to induce constitutive activation of PI3K and downstream of PI3K, Jnk1 and Jnk2, as well as STAT3 and upregulation of STAT3 downstream targets, such as BLCXL and MYC. 55,56 c-KIT mutations have been identified with a particularly high incidence in specific cytogenetic subsets of AML: CBF AML and AML with trisomy 4 (as either the sole cytogenetic aberration or associated with t(8;21)), and are generally not observed in other AML subtypes, such as AML with t(15;17) or with complex karyotype.…”
Section: C-kitmentioning
confidence: 99%
“…Likewise, c-KIT mutations are not equally distributed among FAB subtypes and are mainly found in M1, M4, M4eo and particularly in M2, since nearly 70% of c-KIT-mutated AML patients are classified as M2. [51][52][53][57][58][59] The overall frequency of c-KIT D816 and exon 8 mutations in AML is approximately 2% (33/1940) 58 and 6-8%, [51][52][53][54][55][56][57][58][59] respectively. In contrast, c-KIT D816 and exon 8 mutations have been reported with an average incidence of 16 and 12% among AML patients with t(8;21), and 13 and 22% among AML patients with inv(16), respectively.…”
Section: C-kitmentioning
confidence: 99%
“…These mutations result in constitutively activated FLT3 and its downstream signal pathways, and are associated with elevated blast counts, increased relapse rates and poor overall survival in AML [5][6][7][8]. Mutations of c-KIT and PDGFR are also associated with subsets Nishioka,et al 5 of AML [9][10][11][12]. Therefore, RTK is a therapeutic target and inhibition of activity of RTK may provide a new approach in the treatment of AML patients carrying these mutations.…”
Section: Introductionmentioning
confidence: 99%